(3EOGQI GdehGQO GdHTQjI (B:s (3QDjI eSJbHdjI (B/s - (3eMeO, QGhjI MSfs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2001)
(3JTZjd GdefXe(B- (3JOQjH hJfejI GdGaQGO(B- (3JYhjVGJ GdGaQGO(B- (3HYV GdEJLGgGJ GdMOjKI aj eLGd EOGQI GdehGQO(B.s
Keywords: (3EOGQI GdCaQGOs; (3EOGQI GdehGQO GdHTQjIs; (3GdehGQO GdHTQjIs